Simulações de sustentabilidade e de competitividade da soja no Matopiba - Feitosa, Milena Monteiro (2018)
In the last three decades soya has been one of the most produced and consumed grain in the world. The United States, Brazil and Argentina follow as major world producers of the commodity. In Brazil, specifically in the region of MATOPIBA, composed of the states of Maranhão, Tocantins, Piauí and Bahia, we see a major breakthrough in the production of grain, entering areas not yet explored or the acquisition of the areas of family farmers, causing social and environmental impacts. In this perspective, the present study aimed to simulate economic sustainability capacity of soybean production in that region, if it were not established a ceiling for occupation of this crop. The survey also evaluates the expected soybean production competition capacity in MATOPIBA region comparing the production observed in other Brazilian states and in the United States between the years 1990 and 2016. Specifically the survey sought: assess the economic sustainability of soybean production in MATOPIBA region from 1990 to 2016. The data used in this research are secondary in nature and removed from the Municipal Agricultural Production (PAM), Alice web and the US Department of Agriculture. For estimation of the sustainability index (ISUS) was used factorial analysis method with the technique of principal component decomposition. It was also used, the method proposed by Box and Jenkins (1976) to make soy production expectations in competition of MATOPIBA region. And finally, the survey estimated trend curves to achieve the ultimate goal of progress in the areas cultivated with soybeans on the areas of food crops in the study area. Considering the results obtained in the study, there was breakthrough of the soybean production in MATOPIBA. With simulations of stabilizing areas with soy MATOPIBA the four states (Maranhão, Tocantins, Piauí and Bahia), it was observed that there was a potential sustainability through the growth of crop yield. The results also showed that the formation of soy competition expected in MATOPIBA / US is positive, this is not happening in Brazil, where it was found that the current soybean competitive capacity produced in that region showed a negative evolution of expectations of competitiveness.